Implemetasi Self Reward Terhadap Motivasi untuk Belajar Mahasiswa Akuntansi di STIE Balikpapan - Fadhilah, Arista Avanda; Putri, Bilfina Safira Arum; Farhanah, Refa; Anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the effect of self-reward on the learning motivation of accounting students at STIE Balikpapan. The research method used is a quantitative survey with questionnaires distributed via Google Forms to 10 students in semesters 3, 5, and 7 who were selected using purposive sampling. The research instrument consisted of ten questions covering the form of reward, frequency of application, amount of cost, and its impact on students' enthusiasm, consistency, and academic stress. The results showed that the majority of students felt the positive effects of self-reward, especially in maintaining motivation, increasing enthusiasm for learning, and reducing psychological pressure during lectures. The most common form of reward is buying food or drinks costing between Rp50,000 and Rp150,000, followed by simple activities such as watching movies, resting, or pursuing hobbies. These findings confirm that the effectiveness of self-reward is not determined by the material value, but rather by the personal meaning and emotional satisfaction gained. Thus, self-reward can be used as an effective strategy to build sustainable learning motivation for accounting students in higher education.